A hypothesis: antenatal sensitisation to respiratory syncytial virus in viral bronchiolitis. Issue 6 (1st June 2002) - Legg, J P; Jones, C A; Warner, J A; Johnston, S L; Warner, J O
Abstract : Aim: To investigate the possibility of antenatal sensitisation to respiratory syncytial virus (RSV). Methods: A total of 36 cord blood specimens were obtained from newborn infants; serum IgA was measured to exclude maternal blood contamination. Cord peripheral blood mononuclear cells were separated and cultured in the presence of either uninfected negative control cells or cells containing ultraviolet (UV) inactivated RSV. Proliferation was assessed by tritiated thymidine incorporation. Supernatant cytokine concentrations were measured using ELISA. Results: Significantly higher proliferative response rates to UV inactivated RSV were shown in those infants exposed in utero to the RSV epidemic after 22 weeks gestation. UV inactivated RSV stimulation induced significantly higher interferon γ production from specimens with a positive proliferative response (sensitised) than from those with a negative response (not sensitised). Conclusions: Antenatal sensitisation to RSV occurs in one third of infants exposed to an RSV epidemic at the appropriate time of gestation. This sensitisation is associated with increased interferon γ production, suggesting a type 1 memory response. We hypothesise that priming of fetal T cells to RSV results in a reduced severity of subsequent RSV disease in these individuals and that this will explain much of the clinical diversity of RSV disease.